A Relocatable Ocean Modeling Platform for Downscaling to Shelf-Coastal Areas to Support Disaster Risk Reduction - Trotta, Francesco; Federico, Ivan; Pinardi, Nadia; Coppini, Giovanni; Causio, Salvatore; Jansen, Eric; Iovino, Doroteaciro; Masina, Simona (Frontiers in Marine Science, 2021)
High-impact ocean weather events and climate extremes can have devastating effects on coastal zones and small islands. Marine Disaster Risk Reduction (DRR) is a systematic approach to such events, through which the risk of disaster can be identified, assessed and reduced. This can be done by improving ocean and atmosphere prediction models, data assimilation for better initial conditions and developing an efficient and sustainable impact forecasting methodology for Early Warnings Systems. A common user request during disaster remediation actions is for high-resolution information, which can be derived from easily deployable numerical models nested into operational larger-scale ocean models. The Structured and Unstructured Relocatable Ocean Model for Forecasting (SURF) enables users to rapidly deploy a nested high-resolution numerical model into larger-scale ocean forecasts. Rapidly downscaling the currents, sea level, temperature, and salinity fields is critical in supporting emergency responses to extreme events and natural hazards in the world’s oceans. The most important requirement in a relocatable model is to ensure that the interpolation of low-resolution ocean model fields (analyses and reanalyses) and atmospheric forcing is tested for different model domains. The provision of continuous ocean circulation forecasts through the Copernicus Marine Environment Monitoring Service (CMEMS) enables this testing. High-resolution SURF ocean circulation forecasts can be provided to specific application models such as oil spill fate and transport models, search and rescue trajectory models, and ship routing models requiring knowledge of meteo-oceanographic conditions. SURF was used to downscale CMEMS circulation analyses in four world ocean regions, and the high-resolution currents it can simulate for specific applications are examined. The SURF downscaled circulation fields show that the marine current resolutions affect the quality of the application models to be used for assessing disaster risks, particularly near coastal areas where the coastline geometry must be resolved through a numerical grid, and high-frequency coastal currents must be accurately simulated.